Customer Satisfaction And Reasons For Using Value Added Services Offered By Selected Commercial Banks In Thoothukudi District - A. Devi; Bama, K.Sathya (International Journal of Psychosocial Rehabilitation, 2020)
Banking is a key industry in the service sector. Customer service and Customer satisfaction are the prime work of any system. Value added services have gained greater importance in many days. Commercial banks offer many different channels to access their banking and other services. The value added services not only helps a bank to reduce costs but also helps it to retain its valuable customers. The objective of the study is to analyze the Customer satisfaction and Reasons for using value added services offered by selected commercial banks in Thoothukudi District. Primary data was collected by using questionnaire under purposive random sampling method. 600 sample respondents were selected from Public sector banks like State Bank of India, Indian Bank, Indian Overseas Bank and Private sector banks like ICICI, HDFC and TMB in Thoothukudi District. For analysis purpose Percentage analysis, Score ranking methods and Factor analysis were used.